Utilização do subproduto de processamento do coco na alimentação de cordeiros em confinamento - Silva, Felipe José Santos da (2020)
The use of by-products from the fruit agroindustrial in the lamb diet is an alternative to lower production costs, as long as that the inclusion limit that does not affect the health and productive performance of these animals. In this context, the objective was to evaluate the use of the coconut processing by-product (CB) in performance, carcass characteristics, meat quality, and histological characteristics of feedlot lambs. For this, two experiments were carried out. In trial I, the effect of inclusion CB on the intake, digestibility, nitrogen balance, and fermentative parameters of lambs in the feedlot was evaluated, and in trial II, the effect of inclusion CB on performance, carcass and meat characteristics, meat fatty acid composition, histological characteristics of the rumen, intestine, kidneys, and liver of animals was evaluated. In trial I, five lambs undefined breed, intact males, with an average initial weight of 25.5±1.68 kg were distributed in a Latin square design (5×5) in five treatments that consisted of inclusion levels CB (0, 5, 10, 15 and 20% in dry matter (DM)). In trial II, thirty-five lambs undefined breed, intact males, with an average initial weight of 16.9±2.93 kg were used in a completely randomized design with five treatments with levels of CB inclusion (0; 4.8; 9.6, 14.4 and 19.2% in the DM). There was a linear decrease (P<0.05) of DM intake (DMI) and total digestible nutrients with the inclusion of CB, but the intake of ether extract (EE) was not affected (P>0.05). The inclusion of CB increased quadratic (P<0.05) the digestibility of EE and crude protein, but did not affect (P>0.05) the digestibility of NDF. The inclusion of CB did not affect (P>0.05) the concentration of acetate (mMol/L and %) in the rumen liquid, however, there was a increased quadratic (P<0.05) for propionate (mMol/L and %), acetate:propionate ratio and butyrate (mMol/L and %). The inclusion of 7.2% of the CB improved the feed efficiency and did not affect the average daily gain, however it reduced the cold carcass weight by 0.60 kg (P<0.05) in relation to basal diet. The intramuscular fat and protein content of meat decreased linearly (P<0.05) with the inclusion of CB, but did not affect (P>0.05) the shear force. The saturated fatty acids (SFA) of meat (mg/100g of meat) decreased linearly with the inclusion of CB in diets. There was a tendency (P=0.0615) to increase the activity of Δ9-desaturase, and the content of 18:2c9, t11 was not changed (P>0.05), however, there was a linear increase (P<0.05) of the 18:1t10 content. The inclusion of CB caused a quadratic increase (P<0.05) in the ruminal papilla height, absorption area, and epithelial thickness, and induced linear growth of the mucous layer and linearly reduced (P<0.05) the submucosal layer, as well as it decreased goblet cells in the small intestine. The inclusion of 7.2% of CB decreases the DMI, however, it increases the concentration of propionate in the rumen, also it decreases the body fat deposits without affecting performance, and most of the carcass and meat characteristics. The inclusion of 7.2% of CB, the amount of SFA decreases and the meat's n-polyunsaturated fatty acids increase relatively, it also affects the composition of fatty acids (FA) with a significant increase in FA-trans, especially 18:1t10. In addition, the inclusion of 7.2% it does not cause changes in the histomorphometric characteristics of the gastrointestinal tract and changes in liver and kidney tissue that compromise negatively performance.